THE INFLUENCE OF FACILITIES AND INFRASTRUCTURE QUALITY AND HUMAN RESOURCE COMPETENCE ON PATIENT SAFETY WITH SAFETY CULTURE AS AN INTERVENING VARIABLE - Ince Rosmini; Dini Indriani S; Leony Martila; M Ahmed; Dian Prawibawa; Vip Paramarta (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Patient safety represents a key indicator of healthcare quality, reflecting the ethical and professional responsibility of hospitals to protect patients from harm during medical care. This study aims to analyze the interrelationship between facilities and infrastructure quality and human resource competence on patient safety, with safety culture serving as an intervening variable. A qualitative approach was employed using a case study design, focusing on hospitals that have actively implemented patient safety programs. Data were collected through in-depth interviews, participant observations, and document analysis, and were examined using thematic analysis to identify patterns and relationships among variables. The results show that adequate and well-maintained facilities form the structural foundation for patient safety, while competent healthcare personnel operationalize safety procedures through technical proficiency, clinical decision-making, and ethical responsibility. Safety culture emerges as a mediating force that unites these two components, fostering shared values of open communication, collective learning, and non-punitive responses to errors. The three factors interact synergistically, creating a sustainable safety ecosystem in which infrastructure quality, professional competence, and organizational culture reinforce one another.